Faktor Sosial dan Ekonomi yang Mempengaruhi Ketahanan Pangan Rumah Tangga - Andi Suci Anita (Universitas Lambung Mangkurat, 2015)
Food security is influenced by social factors and economic , which the social factor is the size of the family , the education level of the head of the family , while the economic factors include income and h_ousehold expenditure . This study aims to essess the social and economic factors that affect household food security and social and economic factors determine the most dominant in the village but Jaro District of Tabalong . The method used is quantitative method is by using multiple linear regression and continued by F test to determine whether all the factors or variables influence jointly on household food security . Results showed that the food security of households affected by income , whilo the factor of the number of families , educational level of the family cJml eac;I, expenditure does not affect the partial. The implication is that any efforts to improve household food security must be sought to improve earnings.